Slavery and manumission - Lewis, David (Oxford University Press, 2015)
This chapter provides an overview of the legal contours of slavery in the ancient Greek world, looking at Homer and Hesiod, Gortyn, Sparta, Athens, and Ptolemaic Egypt. It concludes with an overview of manumission law.